Training In Making Papaya Chips And Tough Chips In Developig Entrepreneurship And Creativity Of The Punggomosi Village Community - Tonasa, Muhamad; Ramadani, Ines (Majalah Pengabdian Indonesia, 2024)
The community in Kecamatan Desa/Kelurahan Punggomosi predominantly works as farmers, with papaya being one of the most common crops. Developing papaya into a marketable product is a key part of the KKN (Community Service Program) activities, aimed at broadening the community's knowledge about business and the utilization of local plants, especially for those in need. The program is expected to enhance skills and mental attitudes necessary for personal development. Empowerment through entrepreneurial training serves as a crucial means to provide knowledge and skills related to better family and community life. Ultimately, this training program aims to influence the development of entrepreneurial skills and foster an entrepreneurial spirit, creating independence in both attitude and business.